1998
DOI: 10.1046/j.1365-2168.1998.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors linked to postoperative morbidity in patients with hepatocellular carcinoma

Abstract: The most important risk factors were not always related to liver function tests, but instead to other coexisting conditions such as diabetes mellitus and operation stress including operating time and blood loss. Therefore, any future treatment strategy of hepatic resection for HCC should make every effort both to evaluate coexisting conditions carefully and to reduce operative stress as far as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(112 citation statements)
references
References 15 publications
6
105
1
Order By: Relevance
“…In addition to this finding, we also observed that the size of tumor and blood transfusion were predictors of major postoperative complications. Blood transfusion has long been associated with tumor recurrence (20,23) and also with morbidity and mortality (7,11,14,28) . KOOBY et al (15) revealed that perioperative blood transfusion is a risk factor for poor outcome after liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this finding, we also observed that the size of tumor and blood transfusion were predictors of major postoperative complications. Blood transfusion has long been associated with tumor recurrence (20,23) and also with morbidity and mortality (7,11,14,28) . KOOBY et al (15) revealed that perioperative blood transfusion is a risk factor for poor outcome after liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the laparoscopic approach is associated with lower intraoperative blood loss due to the haemostatic effect of the positive pressure of peritoneum, meticulous intraoperative manipulations of the tissue under magnification, and smaller abdominal incisions. It was reported that intraoperative blood loss is a major risk factor of postoperative morbidity and death [18].…”
Section: Lrfa Advantagesmentioning
confidence: 99%
“…Imaging examinations include percutaneous abdominal ultrasound, computer tomography, magnetic resonance imaging (MRI), chest Rx, and, in selected cases, positron emission tomography using 18 FDG [12].…”
Section: Patient Preparation For Lrfamentioning
confidence: 99%
“…Because of recent advances in surgery, HCC has shown improved prognosis. 1,2 However, the efficacy of this invasive treatment is limited because almost all patients with HCC also suffer from serious liver dysfunction due to hepatitis and cirrhosis. Several less invasive approaches, such as lipidolization, transarterial embolization, or percutaneous ethanol injection therapy, have been used also to treat HCC, but the therapeutic efficacies of these are also limited.…”
mentioning
confidence: 99%
“…Third, HCC may frequently recur in cirrhotic liver, and thus, repeated injections are necessary to treat HCC. 1,2 An adenovirus vector can achieve a high transduction rate of therapeutic genes, but the gene transfection efficiency by repeated administration of this vector is likely to be reduced by an antiadenovirus antibody. 8 We therefore chose liposomes of the hemagglutinating virus of Japan ( HVJ ) , a viral /nonviral hybrid vector, 9 as a gene transfer vector of HCC because this system has shown a relatively low immunogenicity 10 and repeated gene transfection to liver without reduction of gene transfer efficiency in vivo.…”
mentioning
confidence: 99%